Transcranial direct current stimulation over the sensory‐motor regions inhibits gamma synchrony. Issue 9 (10th March 2019) - Pellegrino, Giovanni; Arcara, Giorgio; Di Pino, Giovanni; Turco, Cristina; Maran, Matteo; Weis, Luca; Piccione, Francesco; Siebner, Hartwig Roman
Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique able to induce plasticity phenomena. Although tDCS application has been spreading over a variety of neuroscience domains, the mechanisms by which the stimulation acts are largely unknown. We investigated tDCS effects on cortical gamma synchrony, which is a crucial player in cortical function. We performed a randomized, sham‐controlled, double‐blind study on healthy subjects, combining tDCS and magnetoencephalography. By driving brain activity via 40 Hz auditory stimulation during magnetoencephalography, we experimentally tuned cortical gamma synchrony and measured it before and after bilateral tDCS of the primary sensory‐motor hand regions (anode left, cathode right). We demonstrated that the stimulation induces a remarkable decrease of gamma synchrony (13 out of 15 subjects), as measured by gamma phase at 40 Hz. tDCS has strong remote effects, as the cortical region mostly affected was located far away from the stimulation site and covered a large area of the right centro‐temporal cortex. No significant differences between stimulations were found for baseline gamma synchrony, as well as early transient auditory responses. This suggests a specific tDCS effect on externally driven gamma synchronization. This study sheds new light on the effect of tDCS on cortical function showing that the net effect of the stimulation on cortical gamma synchronization is an inhibition.